Analyse dynamique tridimensionnelle du pénalty au handball selon le niveau d`expertise et la zone ciblée - Villeger, D.; Watier, B. (Movement & Sport Sciences - Science & Motricité, 2013)
The aim of this study is show differences in handball penalty organization according to expertise levels and target location. Six expert players and eight novice players performed a serie of throw targeting low and high location of the goal. The upper body kinematic was recorded with a Vicon motion analysis system. The results indicated a greater ball velocity for throws targeting the goal low part (18.6 ± 0.7 and 18.4 ± 0.8 m/s vs. 17 ± 0.6 and 17.5 ± 0.7 m/s). Joint torque from inverse dynamic at wrist (1.1 ± 0.6 Nm vs. -0.4 ± 0.3 Nm) and elbow (7.9 ± 5.9 Nm vs. -10.5 ± 7.3 Nm) allowed to differentiate experts and novices. The movement organization depends on the target location and the expertise level.